Scientific advances in the concept of the relationship between irritable bowel syndrome (IBS) and food intolerance - Soares, Rosa Leonôra Salerno; Saad , Maria Auxiliadora Nogueira; Santos , Marcia Maria Sales dos (Seven Editora, 2023)
Irritable bowel syndrome (IBS) continues to be a clinical challenge in the 21st century. It is the most commonly diagnosed gastrointestinal condition and also the most common reason for referral to gastroenterology clinics. 1It can affect up to one in five people at some point in their lives and has a significant impact on quality of life and healthcare utilisation. The diagnosis of IBS is not confirmed by a specific test or structural abnormality. Today, the Rome III Criteria are the gold standard for diagnosing IBS. Several mechanisms and theories have been proposed about its etiology, but the biopsychosocial model is currently the most accepted for IBS. However, about two-thirds of patients with IBS have clinical symptoms induced by food intolerance, including gastrointestinal symptoms such as abdominal pain, bloating, diarrhea, or constipation. Common types of food intolerance include lactose intolerance, gluten intolerance, FODMAP intolerance, and histamine intolerance, among which lactose intolerance and FODMAP intolerance are more common in IBS patients. The exact mechanism by which food intolerance is involved in IBS is not fully understood. The symptom complex would be the result of the interaction between psychological, behavioral, psychosocial and environmental factors. Recently, some studies have shown the possible role of histamine and its relationship with non-allergic intolerance as a mediator of digestive clinical manifestations in patients with IBS.3,4 In this chapter we will discuss the role of food intolerance in IBS through a summary of two articles published by our research group related to the role of food intolerance in the pathogenesis of IBS published in 2004 and 2010,  respectively. 5,6 In these trials, we have already emphasized the importance and frequency of atopy and hyperreactivity in patients with IBS. DOI:https://doi.org/10.56238/innovhealthknow-057